Sweet's syndrome: clinicopathological features of patients treated from 1997 to 2009 at Cassiano Antonio Moraes University Hospital - Vitoria (Espirito Santo) Síndrome de Sweet: achados clínico-patológicos nos pacientes atendidos de 1997 a 2009 no Hospital Universitário Cassiano Antônio Moraes - Vitória (Espírito Santo) - Itamara Assini Eleuterio; Ricardo Montibeler Tiussi; Delio Delmaestro; Lucia Martins Diniz; Elton Almeida Lucas (Sociedade Brasileira de Dermatologia, 2012)
Sweet's syndrome or acute febrile neutrophilic dermatosis is rare in Brazil. It is clinically characterized by painful erythematous nodules, papules or plaques that occur mainly on the neck and upper limbs. Its cause may be unknown (idiopathic form) or it may be associated with malignancies, usually hematologic, or drugs. The authors describe 16 cases of the syndrome. The median age was 36 years, and all patients were white and presented solid lesions, predominantly on the upper limbs and trunk. Histopathological examination of the dermis of all patients revealed predominance of moderate to intense, superficial and deep, diffuse inflammatory infiltrate, mainly consisting of polymorphonuclear neutrophils, with leukocytoclasia. It also revealed changes in the epidermis and hypodermis (neutrophilic hypodermitis), but with no signs of vasculitis in most patients, which was not considered an important finding for diagnosis. Presence of exocytosis of neutrophils was common, favoring the diagnosis of Sweet's syndrome when accompanied by diffuse interstitial neutrophilic dermatitis. A Síndrome de Sweet ou dermatose neutrofílica febril aguda é rara no Brasil, caracterizada clinicamente por pápulas, placas ou nódulos eritematosos, dolorosos, principalmente na região cervical e membros superiores. Pode surgir sem fator desencadeante (forma idiopática) ou associar-se a neoplasias, comumente hematológicas, ou a drogas. Os autores descrevem 16 casos da Síndrome, idade mediana de 36 anos, todos da raça branca, com lesões sólidas predominantes nos membros superiores e no tronco. O histopatológico da derme observou, em todos os pacientes, predomínio de infiltrado inflamatório difuso, superficial e profundo, de moderado a intenso, composto principalmente por polimorfonucleares neutrófilos, com leucocitoclasia, além de alterações na epiderme e na hipoderme (hipodermite neutrofílica), mas sem sinais de vasculite na maioria dos pacientes, não sendo considerada achado importante para o diagnóstico. A presença de exocitose de neutrófilos foi frequente, favorecendo o diagnóstico de Síndrome de Sweet quando acompanhada por dermatite intersticial neutrofílica difusa.